Assessment of GPS positioning performance using different signals in the context of ionospheric scintillation: a month-long case study on Sao Jose dos Campos, Brazil - Christovam de Souza, Ana Lucia [UNESP]; Jerez, Gabriel Oliveira [UNESP]; Camargo, Paulo de Oliveira [UNESP]; Marra Alves, Daniele Barroca [UNESP] (Univ Federal Parana, Centro Politecnico, 2022)
The ionospheric scintillation associated to small-scale irregularities in the ionospheric layer can lead to performance degradation of Global Navigation Satellite Systems (GNSS) signals, and the reduction of positioning accuracy. The influence of the ionospheric layer on the GNSS systems is expected to be different for each signal since it is transmitted on different carrier frequencies. This paper presents the results of a quantitative analysis of the scintillation amplitude of GPS (Global Positioning System) signals at L1, L2 and L5 frequencies, aiming to evaluate the impact of the ionospheric scintillation effects on the GPS frequencies. As the ionospheric scintillation may impact positioning accuracy, we also present an assessment of GPS point positioning using those frequencies. The GPS sample data were collected for 30 days between November and December 2014 at SJCE station located in Sao Jose dos Campos (SP), Brazil. Such a region is subjected to the equatorial anomaly effects being characterized by the occurrence of strong ionosphere scintillation. Considering the quantitative analysis, during the different levels of ionospheric scintillation presented a similar behavior, the magnitude of scintillations is small for the L1 signal and larger for L5. In general, the results confirmed that lower frequencies (L2 and L5) suffer more impact from intense scintillation than L1. Regarding the positioning assessment, the multi-frequency positioning was more accurate than single frequency. Considering dual-frequency positioning, results with L1-L2 were more accurate than those with L1-L5 signals. With single-frequency positioning, the L1 signal was more accurate compared to the L2 frequency.
Keywords: GPS Positioning; Amplitude Scintillation; Ionospheric Scintillation; GPS frequencies